The use of modern technologies to enhance the quality of teaching at higher education institutions - Maftyn, Larysa; Romanyuk, Svitlana; Iliichuk, Liubomyra; Vasylyk, Maryna; Tarangul, Liubov (My University, 2023)
Currently, state-of-the-art technologies contribute to the development of the educational process, which entails the search for new approaches to providing information. The purpose of the study is to identify the effectiveness of using modern technologies to enhance the learning performance in higher education institutions. Attaining the said goal became possible due to calculating the variation coefficient of, the obtained level of knowledge, the Student coefficient as well as the direct standardization method. It was found that the greatest advantage of using modern technologies is the possibility of combining distance and in-class learning. However, the disadvantage is the difficulty of identifying the relevant technologies according to the training program. The elaborated mechanisms for ensuring the learning process were implemented with the help of Blackboard, CourseCraft, Trello, EdApp, Scheduler Maker software. It was established that among students who studied pedagogy and primary school methods (group 1), a high level of knowledge was attained with 71%. Students of group 2, who studied English, achieved a high level with 65% of students. The practical implications of the study lie in the improvement of the learning process at higher education institutions drawing on the use of modern technologies. Prospects for research may be related to comparing the effectiveness of programs used to provide learning with a traditional learning approach. Сучасні технології сприяють розвитку навчального процесу, що пов’язано з пошуком нових підходів до подачі інформації. Встановлено, що найбільшою перевагою від використання технологій є можливість комбінування дистанційного й аудиторного навчання. Недолік полягає у складності знаходження характерних технологій відповідно до програми навчання. Розроблені механізми для забезпечення процесу навчання були реалізовані за допомогою програм Blackboard, CourseCraft, Trello, EdApp, Scheduler Maker.
Використання сучасних технологій підвищення якості освіти у вищій школі
Keywords: digital technologies; comprehensive training; educational materials; level of knowledge